Hybrid educational technologies for forming competences of search and critical analysis among future bachelors in land management and cadastres - Igor D. Rudinsky; Oksana Yu Li (RUDN Journal of Informatization in Education)
Problem statement. The article examines the features of competency development among students within the context of hybrid learning. Particular attention is paid to developing universal skills in information search, critical analysis, and synthesis among future bachelor’s degree students in land management and cadastres during the study of Informatics discipline. Methodology. Using such methods as analysis of scientific literature, pedagogical observation, student surveys, and analysis of academic performance, the authors identified key directions for fostering these competencies within the Informatics course. Results. The study revealed that the use of hybrid educational technologies for developing students’ competencies in information search and critical analysis presents its own set of challenges and opportunities. By integrating various educational technologies, including synchronous and asynchronous learning, as well as individual and group activities, hybrid learning offers a multifaceted approach to education. Conclusion. The proposed methodological recommendations for organizing the educational process, taking these features into account, are of practical value for university instructors training bachelor’s degree students in land management and cadastres. Their implementation can enhance the effectiveness of developing the specified competencies within the hybrid learning framework.